Online safety and identity: navigating same-sex male social "dating" apps and networks. Issue 3 (2nd September 2022) - Giles, Cameron; Ashford, Chris; Brown, Kevin J.
ABSTRACT: For gay, queer and bisexual men, and men who have sex with men (MSM), the presence of apps such as Grindr, Scruff, Tinder, Recon, and others have long represented a complex online ecosystem in which identities are formed and constructed in a space intensely governed by social, contractual, and – increasingly – criminal law backed regulation and norms. The publication of the UK Government's Online Safety Bill in late 2020 and revised Bill in March 2022 marked a further legal and policy intervention in regulating online harms to improve safety. It follows other interventions, notably the Criminal Justice and Court Act 2015, which criminalises intimate image sharing in cases where it is done without consent and intends to cause distress. This article draws on original focus group data to examine the navigation of these "Dating" Apps and Networks by their users from a novel perspective arguing that the current legal approach risks both over and under-legislating what is a complex and subtle online ecosystem. It focuses on the construction of identities – the characteristic proxies deployed, management of location-aware features, visuality, and images (re)shared. We seek to provide an essential counterpoint to existing and dominant narratives relating to online safety and identity regulation.